2005
DOI: 10.1007/s10544-005-6076-9
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Three Dimensional Radio Frequency (RF) Shielded Containers for Cell Encapsulation

Abstract: Abstract. This paper describes the construction of three dimensional (3D) encapsulation devices in large numbers, using a novel selfassembling strategy characterized by high mechanical stability, controlled porosity, extreme miniaturization, high reproducibility and the possibility of integrating sensing and actuating electromechanical modules. We demonstrated encapsulation of microbeads and cells within the containers, thereby demonstrating one possible application in cell encapsulation therapy. Magnetic reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
63
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 31 publications
1
63
0
Order By: Relevance
“…Our microgrippers represent an image-guided platform, and techniques such as magnetic resonance imaging or computed tomography will be needed for in vivo guidance. One highlight here is that our microgrippers are metallic; hence, these structures can be easily imaged by using magnetic resonance techniques (33) and specifically wirelessly heated by using electromagnetic fields (34). Another possible complication is that the grippers may become lodged in tissue before reaching the target destination, though we have observed, remarkably, that the grippers can be moved over large distances over certain types of tissue without becoming entangled (Fig.…”
mentioning
confidence: 89%
“…Our microgrippers represent an image-guided platform, and techniques such as magnetic resonance imaging or computed tomography will be needed for in vivo guidance. One highlight here is that our microgrippers are metallic; hence, these structures can be easily imaged by using magnetic resonance techniques (33) and specifically wirelessly heated by using electromagnetic fields (34). Another possible complication is that the grippers may become lodged in tissue before reaching the target destination, though we have observed, remarkably, that the grippers can be moved over large distances over certain types of tissue without becoming entangled (Fig.…”
mentioning
confidence: 89%
“…Gagler [21] and Gracias et al [23][24][25][26][27][28][29][30][31] showed that the surface tension of evaporating drop of liquid is sufficient to pull the walls of the photolithographically defined thin film patterns together and form various figures, such as boxes or pyramids with the size of several micrometers. These patterns typically consist of more rigid areas connected by thinner areas, which serve as hinges, when the thicker walls fold.…”
Section: Surface Tensionmentioning
confidence: 99%
“…Examples of self-folding micro-origami structures (left and middle picture reproduced with permission from Ref. [21] and the right picture from [23]). …”
Section: Surface Tensionmentioning
confidence: 99%
See 2 more Smart Citations